Supporting Technology Integration for School Leaders - Pitler, Howard (Open textbook library.)
This Open Educational Resource (OER) textbook is written as the primary resource for a 3-hour graduate course delivered online by The Teachers College at Emporia State University. The course is designed to prepare school leaders (teachers, instructional coaches, administrators, etc.) for the integration and application of diverse educational technologies into classrooms and schools in ways that reflect a theoretical, research-based, and practical understanding of curriculum development and the effective uses of technology. The course explores practical ways to integrate technology into both teaching and learning and the critical importance of adequate training and professional development for successful integration. This intensive course is delivered completely online over a seven-week period using Canvas. Canvas is a web-based learning management system or LMS. It is used by learning institutions, educators, and students to access and manage online course learning materials and communicate skill development and learning achievement.